1998
DOI: 10.1117/12.320119
|View full text |Cite
|
Sign up to set email alerts
|

<title>Perceptual factors in stereoscopic displays: the effect of stereoscopic filming parameters on perceived quality and reported eyestrain</title>

Abstract: Within the area of broadcasting and entertainment, stereoscopic displays are used to heighten the viewers sense of excitement and quality. To evaluate these subjective experiences, an appreciation-oriented approach seems to be appropriate. Within this framework, this paper reports on two experiments in which we investigated the influence of image disparity, convergence distance and focus length on the subjective assessment of depth, naturalness, quality and eye-strain.Twelve observers with normal or corrected-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…Each clip was rated independently after its presentation, and the time used for rating was not limited. The test subjects were asked to rate the test stimulus according to three criteria separately: the general image quality, naturalness and perceived depth [9]. An integer scale in the range of -3 to 3 was used for the rating.…”
Section: Test Proceduresmentioning
confidence: 99%
“…Each clip was rated independently after its presentation, and the time used for rating was not limited. The test subjects were asked to rate the test stimulus according to three criteria separately: the general image quality, naturalness and perceived depth [9]. An integer scale in the range of -3 to 3 was used for the rating.…”
Section: Test Proceduresmentioning
confidence: 99%
“…Different studies revealed improved usefulness of 3D images over 2D images. 15,16 By incorporating several depth levels we investigated whether the shift between quality of depth and naturalness of depth as found by IJsselsteijn et al 12,13 , is reproduced when assessing overall quality and naturalness. Besides the depth manipulation, we also varied the chroma value per pixel of the originals, creating more and less colorful images.…”
Section: Introductionmentioning
confidence: 99%
“…Participants evaluated the quality of depth and naturalness of depth of stereoscopic images with different depth levels. 12,13 Both quality of depth and naturalness of depth increased with increasing disparity, yet decreased at the extreme depth levels, resulting in an inverted 'U-shape' function. Additionally, preference in quality was shifted to higher depth levels in comparison to preference in naturalness.…”
Section: Introductionmentioning
confidence: 99%
“…The camera separation of 5 cm was found to be the best for the other sequences. With the Dog sequence, the other tested camera separations (10,15,20, and 25 cm) resulted into a an average score close to that of the 5-cm camera separation, while more variation of the results was discovered with the other sequences having the same camera separations, although camera separation 25cm was not available for Newspaper. The camera separations corresponding to the best average scores were used in all subsequent tests.…”
Section: Preparation Of the Test Stimulimentioning
confidence: 83%
“…Each clip was rated independently after its presentation, and the time used for rating was not limited. The test subjects were asked to rate the test stimulus according to three criteria separately: the general image quality, naturalness, and perceived depth [10]. An integer scale in the range of -3 to 3 was used for the rating and after each single observation all three criteria were evaluated.…”
Section: Test Proceduresmentioning
confidence: 99%